Day-to-day experience in resolution of pain after surgery. Issue 11 (November 2017) - Houle, Timothy T.; Miller, Scott; Lang, Jason E.; Booth, Jessica L.; Curry, Regina S.; Harris, Lynnette; Aschenbrenner, Carol A.; Eisenach, James C.
Abstract : Abstract: We know little about the individual pain experience of patients recovering from surgery in the first weeks after hospital discharge. Here, we examine individual differences in the day-to-day experience after 2 major surgeries: lower limb total major joint arthroplasty (TJA) and cesarean delivery (CD). Fifty-five TJA patients and 157 CD patients were recruited to complete questionnaires and record their daily pain experiences after surgery. After hospital discharge, patients recorded their pain intensity once daily for 60 days (CD) or twice daily for 2 weeks, once daily for 2 weeks, weekly for 8 weeks, and monthly for 3 months (TJA). Pain scores were modeled using growth curve and Bayesian change-point models. Individual differences in the model fits were examined for evidence of day-to-day differences in pain. A log time model was the simplest model that fit the data, but examination of the residuals revealed high autocorrelation representing misspecification. A change-point model fit the data better and revealed that the form of recovery fundamentally changed between days 10 and 21 after surgery. These data add meaningfully to our understanding of recovery from pain after surgery by extending the period of frequent observations a few days after surgery to a 2-month period. These high time resolution data suggest that there is a typical experience of pain resolution after surgery, but that meaningful subpopulations of experience may exist. They also indicate that a transition occurs within 1 month after surgery from 1 pattern of change in pain over time to another. Abstract : Pain resolves differently among people after surgery, with some individuals having slow resolution meeting definition of chronic pain. Yet, we know little about the time course of recovery from pain when it is changing most, in the first 2 months after surgery. Here, we acquired high–time-resolution pain evaluations from patients after orthopedic and obstetric surgery and applied growth curve and change-point modeling to the patterns of recovery. In general there is a log(time) pattern to pain intensity scores after major surgery, with a change to a different pattern occurring 10 to 21 days after surgery.